2017
DOI: 10.1017/bpp.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural economics, consumer behaviour and consumer policy: state of the art

Abstract: Counter to the traditional assumption of neoclassical economics that individuals are rational Homo oeconomici that always seek to maximize their utility and follow their 'true' preferences, research in behavioural economics has demonstrated that people's judgements and decisions are often subject to systematic biases and heuristics, and are strongly dependent on the context of the decision. In this article, we briefly review the transition of research from neoclassical economics to behavioural economics, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 81 publications
1
49
0
2
Order By: Relevance
“…The research in psychology, behavioural economics and consumer behaviour has shown that consumers usually display “bounded rationality” in decision making, which means that they are constrained by limited knowledge, resources and time, and are not always able to acquire and process all the necessary information to trade‐off the various available alternatives (Kahneman, 2003; Reisch & Thøgersen, 2017; Simon, 1955). As a result, consumers may not act to the best of their interests (Reisch & Zhao, 2017). The literature in the field of bounded rationality is extensive, and it covers a wide variety of domains and issues, including energy consumption and efficiency (Blasch, Boogen, Filippini, & Kumar, 2017; DellaVigna, 2009; Palmer & Walls, 2015).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The research in psychology, behavioural economics and consumer behaviour has shown that consumers usually display “bounded rationality” in decision making, which means that they are constrained by limited knowledge, resources and time, and are not always able to acquire and process all the necessary information to trade‐off the various available alternatives (Kahneman, 2003; Reisch & Thøgersen, 2017; Simon, 1955). As a result, consumers may not act to the best of their interests (Reisch & Zhao, 2017). The literature in the field of bounded rationality is extensive, and it covers a wide variety of domains and issues, including energy consumption and efficiency (Blasch, Boogen, Filippini, & Kumar, 2017; DellaVigna, 2009; Palmer & Walls, 2015).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…On one hand, these differences indicate deeper conflicts, as different groups within the field compete for both material resources and the power to establish a legitimate definition of consumer research. International debates on "evidence-based consumer policy" are notably dominated by behavioral scholars (Hagen et al, 2013;Reisch & Sandrin, 2015;Reisch & Zhao, 2017), and "behavioral insight teams" have influenced the consumer policy of the European Commission with increasing frequency. However, consumer policy can draw on a wide array of scientific approaches and methods and, consequently, should not be restricted to a single scientific perspective (see also Nessel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Innovation adoption behavior is influenced by several characteristics (Rogers, 2015) and these characteristics related with marketing theory (Reisch & Zhao, 2017). So, it can be reference for website service (Kumar & Sachan, 2017).…”
Section: Relation Behavior Satisfaction and Innovationmentioning
confidence: 99%